Some Coefficient Inequalities of q-Starlike Functions Associated with Conic Domain Defined by q-Derivative - Shahid Mahmood; Mehwish Jabeen; Sarfraz Nawaz Malik; H. M. Srivastava; Rabbiya Manzoor; S. M. Jawwad Riaz (Journal of Function Spaces)
This article deals with q-starlike functions associated with conic domains, defined by Janowski functions. It generalizes the recent study of q-starlike functions while associating it with the conic domains. Certain renowned coefficient inequalities in connection with the previously known ones have been included in this work.